(untitled) (World Bulletin of Public Health, 2024)
Degenerative-dystrophic spine diseases (DDD) are one of the main causes of relative disability and mainly affect people of working age. The incidence of degenerative-dystrophic diseases in medical institutions is 51.2 per 1000 inhabitants. Degenerative-dystrophic diseases of the spine account for up to 40% of all orthopaedic diseases. That is, this pathology is the leading pathology and accounts for 90% of the total number of diseases of the spinal column. And these figures continue to grow from year to year.